2020
DOI: 10.1002/smtd.202000454
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Optical Properties of Nickel‐Oxide Films for Efficient Perovskite Solar Cells

Abstract: Efficient hole transport layer (HTL) is crucial for realizing efficient perovskite solar cells (PSCs). In this study, nickel‐oxide (NiOX) thin‐films are investigated as a potential HTL for PSCs. The NiOX films are prepared by electron‐beam physical vapor deposition at low temperatures. The crystalline properties and the work function are determined by X‐ray diffraction and photoelectric yield spectroscopy. The transmission and the complex refractive index of the films are determined by optical spectroscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 62 publications
0
36
0
1
Order By: Relevance
“…The optical constants of materials were either determined through ellipsometry measurement or adopted from the earlier published work. [18,35] The complex refractive index of materials is provided in Supporting Information (Figure S4, Supporting Information). The optical wave propagation for the device was modeled for a wavelength ranging from 300 to 800 nm close to the perovskite absorber bandgap.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optical constants of materials were either determined through ellipsometry measurement or adopted from the earlier published work. [18,35] The complex refractive index of materials is provided in Supporting Information (Figure S4, Supporting Information). The optical wave propagation for the device was modeled for a wavelength ranging from 300 to 800 nm close to the perovskite absorber bandgap.…”
Section: Methodsmentioning
confidence: 99%
“…More details on the FEM simulation can be found in the Section S2, Supporting Information, and the literature. [35,55] Furthermore, several key electronic properties of the material needed for FEM calculation were compiled from previous experimentally determined values reported in the literature [18] and are summarized in Table S1, Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Введенные атомы никеля легко формируют кластеры как в приповерхностной области, так и в объеме [1]. Эти кластеры действуют как геттерирующие центры [17,18] для различных неконтролируемых примесей (O, Cu, Fe, Au) и других дефектов различной природы. Геттерирующие свойства кластеров в приповерхностной области будут очень заметными из-за высокой концентрации атомов никеля.…”
Section: обсуждение результатовunclassified
“…Perovskite solar cells (PSCs) have shown rapid and immense enhancement in power conversion efficiency (PCE), majorly attributed to carrier mobility [2]. The PSCs have exceptional optoelectronic properties due to low cost [3], rapid extraction, the transportability of the electron transport layer (ETL), and the electron blocking properties of the hole transport layer (HTL) [4][5][6]. Studies have shown that the engineering of interfaces and contact layers leads to the enhanced photovoltaic performance of PSCs [7].…”
Section: Introductionmentioning
confidence: 99%